## Step 1: Step 1: Subtract

The first step is to subtract 2 from both sides of the equal sign:

3x + 2 = 8

-2 -2

Which leaves us:

3x = 6

3x + 2 = 8

-2 -2

Which leaves us:

3x = 6

## Step 2: Step 2: Divide

In Step 2, we divide both sides by the coefficient in front of x:

3x = 6

/3 /3

Which gives us:

x = 2

3x = 6

/3 /3

Which gives us:

x = 2

## Step 3: Step 3: Check Your Solution

In the final step, we will check our solution by plugging our answer back in to the original equation:

3(2) + 2 = 8

We simplify this according to PEMDAS

6 + 2 = 8

8 = 8

Since we get the same number on both sides, we know the solution x = 2 is correct!

3(2) + 2 = 8

We simplify this according to PEMDAS

6 + 2 = 8

8 = 8

Since we get the same number on both sides, we know the solution x = 2 is correct!

x^2+x-2=0 <br>x^2+x-2+2=0+2 <br>(x*x)+x=2 <br>x=1 <br>(1*1)+1=2 <br>(1)+1=2 <br>

x^2+x-2=0 <br>1^2+1-2=0

Fine solution. Could you add some material that helps the person understand what it means to solve the equation and why you do the steps you do and how you choose the order.

That's a good idea. I'll try to find some time to flesh this out soon. <br>

Good! <br>The next step is how to solve x^2+x-2=0 <br>;-) <br> <br>I'm kidding ... however good explanation!